Assessment of electromagnetic interference suppression performance of ferrite core loaded power cord - Zhao, Y. (2013)
An evaluation methodology of the electromagnetic interference (EMI) suppression performance of a ferrite core clamped onto a power cord under its actual operating condition is proposed. With known electrical parameters of a ferrite core, the true EMI suppression performance of the ferrite core at a specific location on a power cord under its intended operating condition can be determined. Based on a two-probe inductive coupling approach, the current probes are clamped on the power cord and the EMI attenuation of a ferrite core loaded power cord can be assessed more objectively without the actual operation interrupted. Taking into account the common-mode impedance of the ferrite core and the common-mode impedances of the power cord terminated with the intended source and load, the true EMI suppression performance of the ferrite core located at different positions along the power cord can be evaluated with confidence. The measured EMI suppression has also been validated with the simulation results using the transmission line model